Difficulty for Students to Complete their Studies for the Licenciate at the Catholic Teachers College, Baucau, Timor-Leste - Moreira Freitas, Agata (Journal of Information System and Education Development, 2025)
The objective of this research was to analyse reasons why postgraduate students at the Instituto Católico para a Formação de Professores (ICFP), translated from Portuguese as Catholic Teachers College, Baucau, face difficulties in continuing their studies. This study used the qualitative method for research and analysis. The data collection guidelines involved interviews with different sources, including six postgraduate students, one representative lecturer, and one parent, to make the data valid and credible. The thematic analysis was applied to analyse the obtained data. This research indicates that students need to extend their studies due to various difficulties, such as balancing double responsibilities, academic problems, personal issues, job status problems, financial difficulties, and low motivation. These difficulties become significant obstacles that cause students to prolong their studies. Based on the study results, the research concluded that the problems and difficulties are situational conditions that hinder postgraduate students from completing their studies and obtaining their postgraduate diploma within the appropriate timeframe.